Tim‐3 suppresses autoimmune hepatitis via the p38/MKP‐1 pathway in Th17 cells. Issue 5 (1st April 2021) - Wu, Hongwei; Tang, Shiyue; Zhou, Mengya; Xue, Jiji; Yu, Zhenjun; Zhu, Jiansheng
Abstract : T‐cell immunoglobulin‐ and mucin‐domain‐containing molecule‐3 (Tim‐3) mediates T‐cell suppression in various autoimmune diseases, such as chronic inflammatory liver disease. However, the regulatory effect of Tim‐3 on Th17 cells in autoimmune hepatitis (AIH) is incompletely understood. Here, we studied the expression and function of Tim‐3 in T cells in AIH patients and in a Con A (concanavalin A)‐induced mouse AIH model. We report that the frequency of CD4 + Tim‐3 + T cells in peripheral blood samples of AIH patients was lower than that in the control group. The p38/MKP‐1 and p‐JNK pathways were activated, and the expression of interleukin‐17A protein was elevated in patients with AIH. Furthermore, the extent of pathological damage in the livers of mice with a blocked Tim‐3 signaling pathway (anti‐Tim‐3 group) was markedly increased and correlated with elevated alanine aminotransferase and aspartate aminotransferase levels. In addition, the frequency of CD4 + IL‐17 + T (Th17) cells in the anti‐Tim‐3 group was increased, while that in mice with blocked p38 activity was decreased. Finally, the expression of MKP‐1 (p‐p38) gradually increased in the control, Con A, and anti‐Tim‐3 groups, but the levels of interleukin‐17A were decreased in the p38‐blocked group. In summary, our results suggest that Tim‐3 suppresses AIH by regulating Th17 cells through the p38/MKP‐1 pathway. Abstract : The regulatory effect of Tim‐3 on Th17 cells in autoimmune hepatitis (AIH) is incompletely understood. In this paper, the expression and function of Tim‐3 in T cells in AIH patients and in a concanavalin A‐induced mouse AIH model were investigated. Our results suggest that Tim‐3 suppresses AIH by regulating Th17 cells through the p38/MKP‐1 pathway.